Ibero-American journals of documentation and communication: thematic intersections and disciplinary confluences in scientific production - Paz Enrique, Luis Ernesto (Scripta Mundi, 2026)
Ibero-American scientific production in the fields of documentation and communication shows sustained growth but faces challenges related to disciplinary fragmentation, limited regional collaboration, and the low visibility of its results. Understanding thematic intersections and citation patterns allows for the identification of conceptual cores that structure this interdisciplinary field. The study aimed to characterize the scientific output of Ibero-American journals in documentation and communication indexed in Scimago Journal & Country Rank, with the purpose of identifying thematic intersections and confluences between both disciplines. A bibliometric and content analysis was conducted on Ibero-American publications in documentation and communication listed in Scimago Journal & Country Rank, focusing on citation frequency, geographic origin of contributions, and term co-occurrence to determine areas of disciplinary convergence. Spain clearly leads in both production and citation, followed by the United Kingdom and Brazil. The most cited papers address journalistic innovation, the political use of social networks, and digital marketing strategies on online platforms. The most frequent keywords were “social media,” “communication,” “disinformation,” and “artificial intelligence,” reflecting the centrality of digital communication, media literacy, and knowledge management. The study concludes that there is evidence of a consolidation of interdisciplinarity between documentation and communication, oriented toward innovation, information verification, and open science. It highlights the need to strengthen regional academic networks and editorial policies that promote collaboration and international visibility.
Keywords: Digital communication; Interdisciplinarity; Scientific production; Media literacy; Open science